A Study Related to Effects of the Brucellosis on Osteoporosis - Hakan Sezgin Sayiner; Sadık Akgün; Yunus Küçükkaya; Murat Alper Başaran; Hüseyin Vural (Medical Laboratory Technology Journal, 2020)
Brucellosis is one of the infectious diseases that may increase osteoporosis risk. Bone formation and destruction markers analyzed in the examination of osteoporosis risk. There been many studies on the effect of a variety of diseases on the bone, but no studies have conducted for brucellosis. This study is one of the rare studies showing the effect of brucellosis on a bone. The purpose of this study is that whether age, agglutination level, having brucellosis at the time or before, and gender knowledge of patients have effects on osteoporosis by using bone formation and destruction markers. Between 01/04/2015 and 31/12/2017, blood samples were taken from 40 patients with brucellosis and seven patients whose treatment completed at least six months before. Then biochemical markers were studied on these blood samples. ELISA washer and reader (Biotek, Novatek, Istanbul, Turkey) was used to obtain the values of bone formation and destruction markers. There was a significant difference, according to H. Osteocalcin (Human Osteocalcin/Bone Gla Protein), in terms of bone formation markers and was higher in women. Having brucellosis at the time was significant according to Human deoxypyridinoline (DPD) and Human C-telopeptide of type I collagen (CTX-I) in terms of bone destruction markers and was higher in brucellosis. The bone formation and destruction markers strongly correlated with each other in the same direction. It is thought that brucellosis can increase bone destruction markers, especially DPD (Human deoxypyridinoline) and CTX-I; therefore, osteoporosis risk in brucella patients can reduce by implementing a treatment plan that closely monitors bone destruction markers.